Genes and proteins of the alternative steroid backdoor pathway for dihydrotestosterone synthesis are expressed in the human ovary and seem enhanced in the polycystic ovary syndrome. (5th February 2017) - Marti, Nesa; Galván, José A.; Pandey, Amit V.; Trippel, Mafalda; Tapia, Coya; Müller, Michel; Perren, Aurel; Flück, Christa E.
Abstract: Recently, dihydrotestosterone biosynthesis through the backdoor pathway has been implicated for the human testis in addition to the classic pathway for testosterone (T) synthesis. In the human ovary, androgen precursors are crucial for estrogen synthesis and hyperandrogenism in pathologies such as the polycystic ovary syndrome is partially due to ovarian overproduction. However, a role for the backdoor pathway is only established for the testis and the adrenal, but not for the human ovary. To investigate whether the backdoor pathway exists in normal and PCOS ovaries, we performed specific gene and protein expression studies on ovarian tissues. We found aldo-keto reductases (AKR1C1-1C4), 5α-reductases (SRD5A1/2) and retinol dehydrogenase (RoDH) expressed in the human ovary, indicating that the ovary might produce dihydrotestosterone via the backdoor pathway. Immunohistochemical studies showed specific localization of these proteins to the theca cells. PCOS ovaries show enhanced expression, what may account for the hyperandrogenism. Graphical abstract: The ovary produces androgens through the backdoor pathway, which may be overactive in PCOS. Highlights: The human testis is able to produce androgens through the backdoor pathway. Whether the backdoor pathway exists in the human ovary is unknown. The specific genes and proteins of the backdoor pathway are expressed in the ovary. Higher expression of backdoor pathway genes and proteins is observed in PCOS. These data hint a role of the backdoor for androgen synthesis in the ovary.